Antibacterial Activity of Ethanol Extracts from Leaves and Flowers of Katang-Katang Ipomoea pes-caprae (L) R.Br Against Pseudomonas aeruginosa - Wibowo, Risky Hadi; Nabella, Inastia; Fitri, Sabrina; Rahmawati, Suci; Hermansyah, Oky; Masrijal, Camelia Dwi Putri; Slamet, Samwilson; Mashudi, Mashudi; Hidayah, Thoriqul (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
The resistance character and infection pathogenicity of bacteria to humans is currently increasing, so there is a need for new alternative drugs. The bioactive compounds contained in katang-katang plant are one of the new sources of antibacterials obtained from nature. This study used leaves and flower samples of Katang-katang (Ipomoea pes-caprae (L)R.Br) obtained from the coastal area of Bengkulu City. The purpose of this study was to determine the phytochemical compounds of the leaves and flower extracts of Katang-katang using color reaction test method and to determine the antibacterial activity of the extracts of the leaves and flowers of Katang-katang against the testing pathogenic bacteria (Pseudomonas aeruginosa) at concentrations of 10%,25%,50%,75% using disc diffusion method. The leaves and flowers ethanolic extracts of the Katang - katang were proven contain secondary metabolites such as alkaloids, flavanoids, saponins, tannins and steroids. Antibacterial effectiveness of the ethanol extract from leaves was classified as moderate at a concentration of 50% with a measured inhibition zone of  6.30 mm and a concentration of 75% with an inhibition zone size 8.13 mm. In contrast, effectiveness of the antibacterial extracted from flower was classified as weak at a concentration of 50% with an inhibition zone 4.50mm and moderate at a concentration of 75% with a measured inhibition zone size of 6.40 mm. The experiment revealed that the leaves and flowers of the Katang-katang have antibacterial potential against P. aeruginosa which could be developed as a medicinal ingredient in the future